A Phase 2 Study of the Hsp90 Inhibitor AUY922 as Treatment for Patients with Refractory Gastrointestinal Stromal Tumors. (2nd July 2016) - Bendell, Johanna C.; Bauer, Todd M.; Lamar, Ruth; Joseph, Mathew; Penley, William; Thompson, Dana S.; Spigel, David R.; Owera, Rami; Lane, Cassie M.; Earwood, Chris; Burris, Howard A.
ABSTRACT: Background : AUY922 is an inhibitor of heat shock protein 90 (Hsp90). Hsp90 inhibitors induce kit degradation in preclinical gastrointestinal stromal tumor (GIST) models. This trial was designed to determine the progression-free survival (PFS) of patients with GIST refractory to or intolerant of imatinib and sunitinib. Methods : Eligible patients received AUY922 70 mg/mg 2 by intravenous (IV) infusion on days 1, 8, and 15 of 21-day cycles. Treatment continued until progression or unacceptable toxicity. Results : Between December 2011 and January 2015, 25 patients were enrolled (median age, 63 years; 56% male) and received a median of 2 cycles (range: 1–12) of AUY922 treatment. Thirty-four patients were planned, but enrollment was stopped early due to slow accrual. Median PFS was 3.9 months (95% CI: 2.5, 5.3) and median OS was 8.5 months (95% CI: 5.2, 16.7). Radiographic response was evaluated in 21 patients; one patient achieved PR (4%) with another 15 having best response of stable disease (60%). The most common treatment-related adverse event was diarrhea (60% all grades). Reversible ocular toxicities that resulted in drug hold (24%) or reduction (8%) were also observed. Conclusion : AUY922 produced a median PFS which compares favorably to historical controls of placebo (6 weeks) for patients refractory to treatment with imatinib. While diarrhea and ocular toxicities were common, the majority of patients received treatment until disease progression.